2006
DOI: 10.1111/j.1442-2042.2006.01663.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of laparoscopic nephrectomy in patients with three or more comorbidities

Abstract: Objectives: Laparoscopic surgery for kidney treatment is a common procedure. However, the efficacy of this procedure in patients with several comorbidities has not been well investigated. We conducted a retrospective comparison of results of laparoscopic surgery between patients with several comorbidities and patients with no comorbidity to access the efficacy and safety of this procedure. Methods: The subjects were 20 patients with three or more comorbidities (group A) and 46 patients with less than three com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The group also reported an increase in mean atelectasis volume in dependent lung regions of 66%. In evaluating the efficacy and outcomes of laparoscopic versus open nephrectomy, Naya et al reported that the frequency of atelectasis in laparoscopic nephrectomy, as shown by chest radiography, was significantly higher than in open surgery [18].…”
Section: Discussionmentioning
confidence: 99%
“…The group also reported an increase in mean atelectasis volume in dependent lung regions of 66%. In evaluating the efficacy and outcomes of laparoscopic versus open nephrectomy, Naya et al reported that the frequency of atelectasis in laparoscopic nephrectomy, as shown by chest radiography, was significantly higher than in open surgery [18].…”
Section: Discussionmentioning
confidence: 99%
“…These relationships could be utilized to improve access to more effective treatments and to better allocate limited resources. In fact, in the United States, the migration of nephrectomy to high‐volume hospitals is already occurring for various reasons, including not only the limited evidence of volume–outcome relationships but also the increasing demand of technically advanced and resource intensive procedures such as the nephron sparing technique and minimally invasive surgery 14–18 . On the other hand, restricting procedures to high‐volume centers or surgeons, will unmistakably cause difficulty in access to such providers.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in the United States, the migration of nephrectomy to high-volume hospitals is already occurring for various reasons, including not only the limited evidence of volume-outcome relationships but also the increasing demand of technically advanced and resource intensive procedures such as the nephron sparing technique and minimally invasive surgery. [14][15][16][17][18] On the other hand , restricting procedures to high-volume centers or surgeons, will unmistakably cause difficulty in access to such providers. If patients are directed to higher volume institutions, the increased volume will overwhelm the resources of such institutions, thereby rendering these procedures even less accessible.…”
Section: Policy Implications Of Our Studymentioning
confidence: 99%
“…The incidence of kidney cancer has been rising over the last two decades; 2 as a result, the use of laparoscopic renal surgery has also increased. Currently, laparoscopic nephrectomy has become widely accepted as a minimally invasive operation for managing localized renal cancer, and it is considered to be a standard operation for urologists 3–6 . Therefore, it is important to educate urological residents to carry out this procedure safely and accurately.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, laparoscopic nephrectomy has become widely accepted as a minimally invasive operation for managing localized renal cancer, and it is considered to be a standard operation for urologists. [3][4][5][6] Therefore, it is important to educate urological residents to carry out this procedure safely and accurately. One of the benefits of laparoscopic surgery is an operating environment that offers a magnified view and enables the surgeon to clearly see the details of the organs.…”
Section: Introductionmentioning
confidence: 99%